On the abuses by the thesis supervisor in the light of the academic ethos - Świtalska, Agnieszka (Journal of Education Culture and Society, 2020)
The paper will attempt to provide an ethical reflection upon abuses by a thesis supervisor that may occur in interpersonal relationships between a student and his or her supervisor. The abuses will be considered from the perspective of the academic ethos. In this the author will focus upon the actual notion of ethosand values which are considered as constituent for the ethos of scholars. In the second part of the paper the author will reflect on which of the thesis supervisor’s attitudes constitute a betrayal of these values.